2021
DOI: 10.1136/bmjinnov-2021-000828
|View full text |Cite
|
Sign up to set email alerts
|

Why is Kangaroo Mother Care not yet scaled in the UK? A systematic review and realist synthesis of a frugal innovation for newborn care

Abstract: ObjectiveKangaroo Mother Care (KMC) is a frugal innovation improving newborn health at a reduced cost compared with incubator use. KMC is widely recommended; however, in the UK, poor evidence exists on KMC, and its implementation remains inconsistent.DesignThis Systematic Review and Realist Synthesis explores the barriers and facilitators in the implementation of KMC in the UK.Data sourceOVID databases, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus and Google Scholar were searched.E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…31 Kangaroo care as a reverse innovation should acknowledge the indigenous/traditional roots of the intervention as a decolonial redressment. (Stefani et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Kangaroo care as a reverse innovation should acknowledge the indigenous/traditional roots of the intervention as a decolonial redressment. (Stefani et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…31 Kangaroo care as a reverse innovation should acknowledge the indigenous/traditional roots of the intervention as a decolonial redressment. (Stefani et al 2022). Some of the above therapies come under the umbrella of complementary and alternative medicine (CAM) and the RCM position statement on these therapeutic modalities says that it has been estimated that as many as 87% of women use complementary therapies and/or natural remedies during pregnancy, childbirth and postnatally.…”
Section: Reverse Innovation and Cultural Appropriationmentioning
confidence: 99%
“…A systematic review and realist synthesis of KMC scale-up in the United Kingdom identified lack of training, knowledge and confidence, and absence of clear guidelines as the main barriers. The authors propose a focus on the potential cost-effectiveness of KMC in reducing the need for incubator use [64].…”
Section: Discussionmentioning
confidence: 99%
“…8 Qualitative studies show that clear guidelines, procedures, experience and continued education is required to improve HCPs confidence in supporting parents practice KC with their preterm infants. 5,9 Available evidence does not suggest that KC interferes with intensive care no adverse events were reported even when infants receive KC post cardiac surgery. 11 However, in the extremely preterm infants (born at <28 weeks' gestational age), the risk of intraventricular haemorrhage, particularly in the first 72 hours after birth, may be a cause for caution.…”
Section: Discussionmentioning
confidence: 99%